CONSTRUCTION AND VALIDATION OF A SCALE OF PROPENSITY FOR VIOLENT BEHAVIOR (EPCV) - Sánchez Carlessi, Héctor Hugo (2023)
Psychometric study aimed at the development and validation of an instrument to assess the level of propensity for violent behavior. The propensity for violent behavior is considered as the person’s willingness to more persistently present attitudes and behaviors linked to impulsiveness, aggressiveness, anger, and hostility, which could lead them to commit violent acts. The instrument was applied to a sample of 362 men and women, young people and adults from the city of Lima. The test was initially made up of 24 items that have been shown to have judge validity, internal validity in terms of the discrimination power of each item using the extreme group method, as well as reliability using Cronbach’s Alpha method, to be considered. a valid and reliable instrument. The exploratory factor analysis finally determined the acceptance of 13 items. The psychometric properties as well as the results are discussed.